Game-centred study using eigenvector centrality in high-level women's volleyball: play efficacy is independent of game patterns… Or is it? - Laporta, L.; Valongo, B.; Afonso, J.; Mesquita, I. (Montenegrin Journal of Sports Science and Medicine, 2021)
In sports, it is often assumed that distinct game patterns may influence the outcome of the play differently. However, a few articles about men`s volleyball have suggested that play efficacy may rely more on the quality of individual attack actions, and not on game patterns. Therefore, the goal of this paper was to scrutinize if and how game pat-terns influence play efficacy in high-level women`s volleyball. Eigenvector Centrality was assessed to integrate direct and indirect relationships between games actions. Thirteen matches from the women`s World Grand Prix`2015 were analysed (46 sets; 2,016 plays). Actions were categorized according to game complex (K0 to KV) and three levels of the efficacy of each play: error, continuity, and point. The results showed that play efficacy was independent of game patterns (the central pattern was non-ideal setting conditions in all complexes and preference for using slow attacks in the extremities of the net). There were, however, some regularities for each game complex. For example, while in KI to KIII, Zone 4 was the most used attack zone, in KIV and KV there was a complete inversion to Zone 2. Moreover, results revealed that women`s volleyball games are more predictable in relation to the play space (attack zones) while increasing the risk through enhanced game speed (attack tempo), in comparison with what studies in men`s volley-ball have shown. Future studies should consider situational variables (e.g., match status, home vs away matches), and individual players` actions should be considered in order to understand their relationships with team patterns better.